Silek Pangian in the Bolek Laman Tuo Tradition in The Social Structure of The Nagari Sungai Dareh Community, Dharmasraya District, West Sumatra Province - Malindo, Ihsanul Malindo; Wilma Sriwulan (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research, entitled "Silek Pangian in the Bolek Laman Tuo Tradition in the Social Structure of the Nagari Sungai Dareh Community, Dharmasraya Regency, West Sumatra Province", is research on the Silek Pangian performance which is performed on a page tuo in the Bolek Laman Tuo tradition in the Nagari Sungai Dareh community. This research uses performance studies theory by Richard Schechner which is assisted by the concept of performance by Milton Singer. Performance studies theory is used to investigate the Silek Pangian performance in the Bolek Laman Tuo Tradition in the social structure of the Nagari Sungai Dareh community, as a performance that can be observed from various aspects, both from the aspect of the person performing, the audience, and the people who was accidentally present at the incident. Milton Singer's concept of cultural performances helps to analyze that a cultural performance has: (a) limited performance time; (b) beginning and end; (c) organized activity events; (d) a group of players; (e) a group of spectators; (f) performance venue; (g) the opportunity to demonstrate it. This research uses an ethnographic method, which makes the researcher a participant observer in this research. The results of the research show that Silek Pangian in the Bolek Laman Tuo Tradition is a show and performance that has always been part of the social structure of society and has become a tradition that is proud of the local community of Nagari Sungai Dareh, Dharmasraya Regency, West Sumatra Province.